Transfer path analysis: Current practice, trade-offs and consideration of damping. (15th February 2017) - Oktav, Akın; Yılmaz, Çetin; Anlaş, Günay
Abstract: Current practice of experimental transfer path analysis is discussed in the context of trade-offs between accuracy and time cost. An overview of methods, which propose solutions for structure borne noise, is given, where assumptions, drawbacks and advantages of methods are stated theoretically. Applicability of methods is also investigated, where an engine induced structure borne noise of an automobile is taken as a reference problem. Depending on this particular problem, sources of measurement errors, processing operations that affect results and physical obstacles faced in the application are analysed. While an operational measurement is common in all stated methods, when it comes to removal of source, or the need for an external excitation, discrepancies are present. Depending on the chosen method, promised outcomes like independent characterisation of the source, or getting information about mounts also differ. Although many aspects of the problem are reported in the literature, damping and its effects are not considered. Damping effect is embedded in the measured complex frequency response functions, and it is needed to be analysed in the post processing step. Effects of damping, reasons and methods to analyse them are discussed in detail. In this regard, a new procedure, which increases the accuracy of results, is also proposed. Abstract : Highlights: TPA is discussed in the context of trade-offs between accuracy and time cost. Sources of errors are examined. Current practice is applied to an industrial problem: engine-induced noise. The reasons and methods to analyse the effects of damping are discussed in detail. Calculated and measured sound pressure levels are compared.